The epidemiology of gastrointestinal nematode infections in communal cattle and commercial beef cattle on the highveld of Zimbabwe - Moyo, Doreen Z.; Bwangamoi, O.; Hendrikx, W. M. L.; Eysker, M. (Elsevier, 2015)
An epidemiological study of gastrointestinal nematode infections of cattle was conducted on the highveld of Zimbabwe from June 1993 to May 1995. The study was carded out in two communal areas, two conventional beef farms and two commercial beef farms with irrigated pastures. On all farms/areas, faecal egg counts were low ( < 500 eggs per g faeces) during the dry season. During the rainy season faecal egg counts were highest in communal areas and lowest in conventional beef farms. Those of irrigated farms had intermediate values. During the dry season pasture larval counts were low in irrigated pastures and conventional beef farms and virtually zero in communal areas. They increased and peaked during the rainy season, coinciding with the egg count peaks. Worm burdens of necropsied cattle indicated that 100% of the animals were infected with nematodes. The important species were Cooperia pectinata, C. punctata, Haemonchus placei, Trichostrongylus axei and Oesophagostomum radiatum in all farms/areas and Ostertagia ostertagi in a beef farm with irrigated pastures. Haemonchus survived the dry season as inhibited early fourth stage larvae whereas Cooperia and Trichostrongylus survived as adults.